2022
DOI: 10.1093/cid/ciac275
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Disease Severity in Children Infected With the Omicron Variant

Abstract: Background There are limited data assessing COVID-19 disease severity in children/adolescents infected with the Omicron variant. Methods We identified children and adolescents <18 years with SARS-CoV-2 infection with Delta and propensity-score matched controls with Omicron variant infection from the National COVID-19 Database in Qatar. Primary outcome was disease severity, determined by hospital admission, admission to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 28 publications
9
90
1
4
Order By: Relevance
“…Wang et al performed a propensity score matching cohort study in children younger than 5 years in the United States that revealed that risks for hospitalizations and ICU admissions were lower in the patients <5 years old in the Omicron variant predominant period than those in the Delta predominant period. Another propensity matched cohort study conducted in Qatar reported that the patients with the Omicron variant infection had less severe disease [ 17 ]. In our study, more patients required noninvasive oxygen support in the Omicron variant predominant period than in the Delta variant predominant period; however, the ICU admission rates in those two periods were similar and no patients died.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al performed a propensity score matching cohort study in children younger than 5 years in the United States that revealed that risks for hospitalizations and ICU admissions were lower in the patients <5 years old in the Omicron variant predominant period than those in the Delta predominant period. Another propensity matched cohort study conducted in Qatar reported that the patients with the Omicron variant infection had less severe disease [ 17 ]. In our study, more patients required noninvasive oxygen support in the Omicron variant predominant period than in the Delta variant predominant period; however, the ICU admission rates in those two periods were similar and no patients died.…”
Section: Discussionmentioning
confidence: 99%
“…In response, stringent mitigation measures were relaxed worldwide. 39,40 Our data show that this (at least in school settings) apparently led to "catch-up" infections in those thus far protected from infection with SARS- . By the end of our data collection (April 2022), only a small difference in cumulative infection rates was observed between students with strict mask wearing rules during the highincidence period and those without.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, the CNN based on sequential Spike predicting the higher human adaptation of the BA.2 sublineage was consistent with pandemic facts. In the context of COVID-19 disease severity, post-SARS-CoV-2 infection, decreasing pathogenicity was reported by recent variants compared to others in the early stages of the COVID-19 pandemic [ 33 ]. However, there is not yet conclusive about the severity difference between Omicron BA.1 and BA.2 sublineages.…”
Section: Discussionmentioning
confidence: 99%